Molecular aspects of phylogenetic relationships among trypanosoma (Nannomonas) congolense. - Osanya, A. (University of Nairobi, 1995)
At least four different genotypic groups of Trypanosoma (Nannomonas) congolense have been described based upon profiles of iso-enzymes, nucleotide composition of the highly repetitive satellite DNA, restriction fragment length polymorphisms (RFLPs) of conserved nuclear and kinetoplast DNA sequences and, more recently, randomly amplified polymorphic DNA (RAPD) patterns. The exact phylogenetic relationships of these morphologically identical but genetically heterogeneous parasites is obscure. I have designed specific oligonucleotide primers based on conserved nucleotide sequences of 18S ribosomal RNA (18S rRNA) gene of Trypanosoma brucei, Leishmania donovani, Triponema aequale and Lagenidium gigantum, and used these in the polymerase chain reaction (PCR) to amplify genomic DNA from four different clones each representing a different genotypic group of T. congolense. PCR products of approximately 1 kb were generated using as template DNA from each of the trypanosomes. The nucleotide sequences of a segment of the PCR products were determined by direct sequencing to provide partial nucleotide sequence of the 18S rRNA gene in each of the trypanosomes. Using these sequences and those that have been published for the other Trypanosomatids, sequence similarity scores were determined with the help of appropriate computer software. Additionally, primers of arbitrary nucleotide sequence have been employed in the PCR amplification of genomic DNA from the four trypanosome clones representing the different T. congolense types. The patterns of randomly amplified polymorphic DNA (RAPD) have been used in the calculation of pairwise genetic similarity indices among these trypanosomes without making assumptions regarding relative band intensities. In a parallel study I have demonstrated that the PCR products of the 18S rRNA gene are sensitive probes for specific identification of trypanosomes. I have used heterologous PCR products as probes in hybridization analyses of genomic DNA and PCR products from the different types of T. congolense and from other protozoa. The RFLPs observed confirmed heterogeneity of the 18S rRNA gene sequences among the trypanosomes comprising the subgenus Nannomonas.